Method for producing an aerogel blanket and an aerogel blanket produced by the same

The use of a non-toxic sodium base catalyst and acidic surface modification in aerogel blanket production addresses the instability and toxicity issues of ammonia-based methods, resulting in high-quality aerogel blankets with enhanced thermal conductivity and hydrophobicity.

JP7601427B2Active Publication Date: 2024-12-17LG CHEM LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022571857
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-15
Filing Date
2021-10-01
Publication Date
2024-12-17
Estimated Expiration
2041-10-01

AI Technical Summary

Technical Problem

Conventional gel casting methods for producing aerogel blankets using ammonia as a catalyst result in process instability due to toxic gas emissions and require high amounts, leading to poor product quality and increased costs.

Method used

A method utilizing a non-toxic sodium base catalyst and acidic surface modification to catalyze gelation and prevent gel structure collapse during drying, ensuring high thermal conductivity and hydrophobicity.

Benefits of technology

The method produces aerogel blankets with improved thermal conductivity and hydrophobicity, reducing costs and environmental hazards while maintaining structural integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601427000001
    Figure 0007601427000001
  • Figure 0007601427000002
    Figure 0007601427000002
Patent Text Reader

Abstract

The present invention provides a method for producing an aerogel blanket, in which a surface modification step is performed under acidic conditions while using a non-toxic catalyst, thereby eliminating the need for a solvent substitution step or a cleaning step, thereby simplifying the production process, and preventing the gel structure from collapsing due to shrinkage even when drying at normal pressure. The method also provides a method for producing an aerogel with excellent thermal conductivity and hydrophobicity due to high surface modification efficiency, and an aerogel blanket produced thereby, in which hydrophobic groups are uniformly formed inside the substrate, and which has low thermal conductivity and low water absorption.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 2020-0133466 filed on October 15, 2020, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a method for producing an aerogel blanket, which comprises the steps of gelation using a non-toxic base catalyst and a surface modification process under acid conditions, and to an aerogel blanket produced by said method. [Background technology]

[0003] Aerogel is a super-porous, high-specific surface area (≧500m2) material with a porosity of 90-99.9% and pore sizes in the range of 1-100 nm. 2 Aerogel is a material that has excellent properties such as being ultra-lightweight, ultra-insulating, and ultra-low dielectric. Therefore, not only is there much research and development on aerogel materials, but there is also active research being conducted on its applications as transparent insulating materials and environmentally friendly high-temperature insulating materials, extremely low dielectric thin films for highly integrated devices, catalysts and catalyst supports, electrodes for supercapacitors, and electrode materials for seawater desalination.

[0004] The greatest advantage of aerogel is that it has super-insulation properties, exhibiting a thermal conductivity of less than 0.300 W / m K, which is lower than that of conventional organic insulation materials such as polystyrene foam, and that it can resolve the fatal weaknesses of organic insulation materials, namely vulnerability to fire and the generation of harmful gases during a fire.

[0005] Generally, aerogels are produced by producing hydrogels from precursor materials and then removing the liquid components inside the hydrogel without destroying the microstructure. Aerogels are generally produced in powder form, which can be divided into three types: powder, granules, and monoliths.

[0006] The powder can be combined with fibers to produce products in the form of an aerogel blanket or aerogel sheet, and the blanket or sheet can be bent, folded, or cut to any size or shape because it is flexible. Therefore, it can be used not only for industrial applications such as insulation panels for LNG ships, industrial insulation materials, space suits, transportation and vehicles, and insulation materials for power generation, but also for daily necessities such as jackets and sneakers. In addition, when aerogel is used in fire doors as well as roofs and soles in houses such as apartments, it is very effective in preventing fires.

[0007] Specifically, the aerogel blanket in this specification is a concept that refers to a material in which aerogel is impregnated into a blanket substrate such as fiber, and the manufacturing method of the aerogel blanket is divided into a gel casting method and a method in which aerogel powder or granules are manufactured and then deposited on the blanket substrate using a binder.

[0008] Products manufactured by the gel casting method have good physical properties and account for the majority of the usage to date, and a gel casting method using the roll-to-roll technique is known as a currently commercialized technology. Ammonia is generally used as a catalyst for the gelation process, and ammonia is widely used due to its excellent physical properties of aerogel, such as effectively preventing the collapse of the gel structure.

[0009] However, in the case of ammonia catalyst, since it is a weak base component, a large amount must be used to ensure gel time and physical properties in the process, and the toxic gas components reduce process stability and some of them remain in the final product, which is problematic. Therefore, in order to ensure process stability and product environmental friendliness, it is necessary to develop a process and product that can remove toxic substances from the entire process while ensuring physical properties at the same or higher level. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] KR10-2012-0070948A Summary of the Invention [Problem to be solved by the invention]

[0011] The present invention has been made to solve the above-mentioned problems of the related art, and provides a method for producing an aerogel blanket by a gel casting method, in which a sol is catalyzed and gelled using a non-toxic sodium-based base catalyst in the gelation process, and the surface modification process is carried out under acidic conditions, so that the gel structure does not collapse due to shrinkage even when dried at normal pressure, and therefore, a cost reduction effect can be expected compared to supercritical drying, and safety can be ensured by replacing toxic catalysts with non-toxic substances, and the collapse of the gel structure is suppressed by surface modification under acidic conditions, thereby providing a method for producing an aerogel blanket that can sufficiently improve thermal conductivity and hydrophobicity.

[0012] Another object of the present invention is to provide a highly heat-insulating aerogel blanket manufactured by the above-mentioned method for manufacturing an aerogel blanket. [Means for solving the problem]

[0013] The present invention is directed to solving the above-mentioned problems, and provides a method for producing an aerogel blanket, comprising the steps of: 1) mixing silica sol and a sodium-based base catalyst to obtain a catalyzed silica sol; 2) impregnating a blanket substrate with the catalyzed silica sol to gel it, thereby obtaining a wet gel-fiber composite; 3) introducing an acidic surface-modifying solution containing a surface modifier and a chlorine-based acid-derived aqueous solution into the wet gel-fiber composite to hydrophobize it; and 4) drying the hydrophobized wet gel-fiber composite. Effect of the Invention

[0014] The manufacturing method of the present invention has the advantages that in the gelation step, a non-toxic sodium-based base catalyst is used to catalyze gelation of the sol, and the surface modification step is performed under acidic conditions, so that the gel structure does not collapse due to shrinkage even when dried at normal pressure, which can be expected to result in cost savings compared to supercritical drying, and safety can be ensured by replacing toxic catalysts with non-toxic substances, and the collapse of the gel structure is suppressed by surface modification under acidic conditions, making it possible to sufficiently improve thermal conductivity and hydrophobicity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention will be described in more detail below so that the present invention can be easily understood. In this regard, the terms and words used in the specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as having meanings and concepts that are consistent with the technical ideas of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0016] 1. Manufacturing method of aerogel blanket The method for producing an aerogel blanket according to one embodiment of the present invention includes the steps of: 1) mixing silica sol and a sodium-based base catalyst to obtain a catalyzed silica sol; 2) impregnating a blanket substrate with the catalyzed silica sol to gel it, thereby obtaining a wet gel-fiber composite; 3) hydrophobizing the wet gel-fiber composite by introducing an acidic surface-modifying solution containing a surface modifier and a chlorine-based acid-derived aqueous solution; and 4) drying the hydrophobized wet gel-fiber composite.

[0017] The manufacturing method is intended to replace the toxic gelling catalyst used in the existing gel casting method and to solve the problems that arise when replacing the catalyst. Specifically, the toxic ammonia-based catalyst is replaced with a non-toxic sodium-based base catalyst, and a surface modification process is performed under acidic conditions to achieve the thermal conductivity and hydrophobicity that can be achieved when using an ammonia catalyst.

[0018] More specifically, the toxic ammonia-based catalyst is a weak base and therefore needs to be used in large amounts to ensure gel time and physical properties, but the pH during the process is relatively low, so there is no problem of the gel structure collapsing due to shrinkage during drying even if the solvent evaporates. However, in the case of a non-toxic sodium-based base catalyst, since it is a strong base, the pH is increased during the process, so there is a problem of the gel structure collapsing during drying. To solve this problem, the surface modification process is acidified to neutralize the sodium-based base catalyst, which is a strong base, and the pH is lowered by the generation of salt to prevent the gel structure from collapsing, so that an aerogel blanket with high thermal conductivity and hydrophobicity can be manufactured even though a non-toxic catalyst is used.

[0019] In addition, in the above-mentioned manufacturing method, when a sodium-based base catalyst is used, a shrinkage phenomenon occurs severely during drying, making it impossible to apply a drying process at normal pressure, and precise control is required to prevent shrinkage due to supercritical drying. However, by acidifying the surface modification process, it becomes possible to control the shrinkage of the gel structure, making it possible to apply a drying process at normal pressure.

[0020] Furthermore, because the sodium-based base catalyst is a strong base, sufficient gelation can be induced even when a small amount is used, and the surface modification process is acidified. During the surface modification, a neutralization reaction is induced by the formation of a salt with the strong base catalyst, which is an added effect of improving the efficiency of the surface modification.

[0021] Hereinafter, each step of the method for manufacturing the aerogel blanket of the present invention will be described in detail. Step 1: Catalysis The step 1) according to one embodiment of the present invention is a step of mixing silica sol and a sodium-based base catalyst to obtain a catalyzed silica sol.

[0022] In the present invention, the catalyzed silica sol may be prepared by mixing a silica sol with a sodium-based base catalyst, and the base catalyst serves to increase the pH of the silica sol and promote the gelation in step 2).

[0023] The silica sol according to one embodiment of the present invention includes a silica precursor and an organic solvent, and may be prepared by mixing them. The silica sol catalyzed in step 1) may be prepared by mixing the silica sol with a base catalyst, and the silica sol may be prepared by mixing the silica precursor with an organic solvent, and may further include water, or may use a water-containing organic solvent. The silica precursor may be hydrolyzed at a low pH to facilitate gelation, and an acid catalyst may be used to lower the pH.

[0024] The silica precursor that can be used in producing the silica sol may be a silicon-containing alkoxide compound, specifically, tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), methyl triethyl orthosilicate, dimethyl diethyl orthosilicate, tetrapropyl orthosilicate, tetraisopropyl orthosilicate, tetrabutyl orthosilicate, tetra secondary butyl orthosilicate, tetra tertiary butyl orthosilicate, tetrahexyl orthosilicate, tetracyclo ... orthosilicate, tetradodecyl orthosilicate, etc. More specifically, the silica precursor according to an embodiment of the present invention may be tetraethyl orthosilicate (TEOS).

[0025] Furthermore, the acid catalyst that may be further contained in the silica sol according to one embodiment of the present invention is not limited and may be any acid catalyst that adjusts the pH to 3 or less, and examples thereof include hydrochloric acid, nitric acid, and sulfuric acid. In this case, the acid catalyst may be added in an amount that adjusts the pH of the sol to 3 or less, or may be added in the form of an aqueous solution dissolved in an aqueous solvent.

[0026] The silica precursor according to an embodiment of the present invention may be in a state where the silica precursor is hydrolyzed by a preliminary reaction with the acid catalyst. For example, the silica precursor may be tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), methyl triethyl orthosilicate, dimethyl diethyl orthosilicate, tetrapropyl orthosilicate, tetraisopropyl orthosilicate, tetrabutyl orthosilicate, tetra secondary butyl orthosilicate, tetra tertiary butyl orthosilicate, tetrahexyl orthosilicate, or the like. Alternatively, tetraalkyl silicates such as tetracyclohexyl orthosilicate, tetracyclohexyl orthosilicate, tetradodecyl orthosilicate, etc. may be reacted with an acid catalyst to be prehydrolyzed and then immediately applied.

[0027] The silica precursor may be used in an amount such that the content of silica (SiO2) in the silica sol is 3% by weight to 30% by weight. If the content of silica is less than 3% by weight, the content of silica aerogel in the final blanket is too low, which may cause a problem that the desired level of heat insulating effect cannot be expected, and if the content of silica is more than 30% by weight, the mechanical properties of the blanket, especially flexibility, may be reduced due to the formation of excessive silica aerogel.

[0028] In addition, the organic solvent usable in the production of the silica sol of the present invention can be used without any limitation as long as it has excellent compatibility with the silica precursor and water, and specifically, a polar organic solvent may be used, and more specifically, an alcohol may be used. Here, the alcohol may be specifically a monohydric alcohol such as methanol, ethanol, isopropanol, butanol, etc.; or a polyhydric alcohol such as glycerol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, and sorbitol, etc., and any one or a mixture of two or more of these may be used. Among them, in consideration of miscibility with water and the aerogel to be produced in the future, it may be a monohydric alcohol having 1 to 6 carbon atoms such as methanol, ethanol, isopropanol, butanol, etc. The organic solvent may be used in an appropriate amount in consideration of the content of the aerogel to be finally produced.

[0029] The silica sol according to an embodiment of the present invention may contain a silica precursor and water in a molar ratio of 1:4 to 1:1. Also, the silica precursor and the organic solvent may be contained in a weight ratio of 1:2 to 1:9, preferably 1:4 to 1:6. When the silica precursor satisfies the above molar or weight ratio with respect to water and the organic solvent, the production yield of the aerogel can be further increased, and there is an improvement effect in terms of heat insulating performance. Specifically, when the density of the silica precursor in the silica sol is 50 kg / m 3 ~100kg / m 3 Preferably 50 kg / m 3 ~80kg / m 3 More preferably, 60 kg / m 3 ~80kg / m 3 The ratio may be adjusted within the above range so as to achieve the above.

[0030] According to one embodiment of the present invention, the sodium-based base catalyst may be an inorganic base, specifically, sodium hydroxide (NaOH) or sodium silicate, and may be an inorganic base containing sodium, which is generally called a strong base.

[0031] Commonly used amines include ammonia (NH3), ammonium hydroxide (NH4OH; aqueous ammonia), tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH), methylamine, ethylamine, isopropylamine, monoisopropylamine, diethylamine, diisopropylamine, dibutylamine, trimethylamine, triethylamine, triisopropylamine, tributylamine, choline, monoethanolamine, diethanolamine, 2-aminoethanol, 2-(ethylamino)ethanol. In the case of substances containing amines or ammonia, such as ethanol, 2-(methylamino)ethanol, N-methyldiethanolamine, dimethylaminoethanol, diethylaminoethanol, nitrilotriethanol, 2-(2-aminoethoxy)ethanol, 1-amino-2-propanol, triethanolamine, monopropanolamine, dibutanolamine, or pyridine, there is a problem that ammonia is generated during the process and toxic gas is emitted, which can cause serious safety issues. The effects on workers and, if contained in products, the effects on product users are becoming increasingly problematic, and there is a demand for alternatives to such amine or ammonia-based catalysts.

[0032] In the present invention, by using a non-toxic strong base as the sodium-based base catalyst, gelation is possible even with a small amount of use compared to conventional catalysts, and the gelation efficiency can be improved. There are also advantages in that toxic substances are removed during the process, and the gelation time can be reduced, thereby increasing productivity.

[0033] The sodium-based base catalyst may be included in an amount that makes the pH of the sol 9.0 to 11.0. When the pH of the catalyzed silica sol is in the above range, the productivity can be increased by increasing the gelation efficiency and shortening the gelation time in step 2) described below, and there is an advantage that toxic substances are eliminated during the process. In addition, since the sodium-based base catalyst may be precipitated when added as a solid phase, it is preferable to add it as a solution phase diluted with an aqueous solvent or the organic solvent.

[0034] In this case, the dilution ratio of the sodium-based base catalyst and the organic solvent, specifically the alcohol, may be 1:4 to 1:100 based on the volume. In addition, the sodium-based base catalyst may have a sodium ion concentration of 1 mmol / L to 100 mmol / L, preferably 5 mmol / L to 50 mmol / L, based on the volume of the catalyzed silica sol, and the degree of dilution may be an appropriate level required in consideration of the reactivity of the strong base, and the concentration of the sodium ion is preferably applied within the above range as a level that can promote the reaction as a catalyst.

[0035] On the other hand, the sodium-based base catalyst may be in the form of an aqueous solution having a concentration of 10% to 50%, preferably 20% to 40%. According to one embodiment of the present invention, the catalyzed silica sol may further contain an additive, if necessary. In this case, the additive may be any known additive that can be added when preparing an aerogel, such as an opacifying agent, a flame retardant, etc.

[0036] Step 2: Impregnation and gelation process Step 2) according to one embodiment of the present invention is for producing a wet gel-fiber composite (wet gel blanket), and is a step of impregnating a blanket substrate with a catalyzed silica sol and gelling the catalyzed silica sol within the impregnated blanket substrate.

[0037] The step 2) is to impregnate the blanket substrate with the catalyzed silica sol. Various methods may be used, such as using an impregnation tank to impregnate the blanket substrate with the catalyzed sol by feeding the catalyzed silica sol prepared in the step 1) and the blanket substrate into a reaction vessel, using a roll-to-roll technique in which the blanket substrate moves on a conveyer belt and the catalyzed silica sol is sprayed onto the moving blanket substrate, or using a combination of the two methods.

[0038] The term "impregnation" as used in the present invention refers to the introduction of a fluid catalyzed sol into the blanket substrate, and may indicate that the catalyzed sol penetrates into the pores inside the blanket substrate.

[0039] In the step 2) according to one embodiment of the present invention, the order of introduction is not particularly limited as long as the blanket base material and the catalyzed silica sol are introduced into the reaction vessel. Specifically, the step 2) may be introduced in any one of the following methods: introducing the blanket base material into the reaction vessel and then introducing the catalyzed silica sol; introducing the blanket base material into the reaction vessel and then introducing the catalyzed silica sol; and introducing the blanket base material into the reaction vessel while introducing the catalyzed silica sol.

[0040] As another example, step 2) may be performed by spraying the silica sol onto the blanket substrate while the blanket substrate is moving on a conveyer belt, or by combining an impregnation bath with a roll-to-roll method, so that the blanket substrate is impregnated with the catalyzed silica sol and gelled.

[0041] In addition, the blanket substrate according to an embodiment of the present invention may be a porous substrate in terms of improving the thermal insulation of the aerogel blanket. When a porous blanket substrate is used, the catalyzed sol can easily penetrate into the substrate, and the aerogel can be uniformly formed inside the blanket substrate, so that the manufactured aerogel blanket can have excellent thermal insulation.

[0042] The blanket substrate usable in accordance with one embodiment of the present invention may be a film, sheet, net, fiber, foam, nonwoven fabric, or a laminate of two or more layers thereof. In addition, the surface may be roughened or patterned depending on the application. More specifically, the blanket substrate may be a fiber that can further improve the insulation performance by including spaces or pores in the blanket substrate that can easily insert aerogel. In addition, the blanket substrate preferably has low thermal conductivity.

[0043] Specifically, the blanket substrate may be polyamide, polybenzimidazole, polyaramid, acrylic resin, phenolic resin, polyester, polyetheretherketone (PEEK), polyolefin (e.g., polyethylene, polypropylene, or copolymers thereof), cellulose, carbon, cotton, wool, hemp, nonwoven fabric, glass fiber, ceramic wool, or the like. More specifically, in the present invention, the blanket substrate may be glass fiber (glass felt, glass fiber).

[0044] In step 1), when the catalyzed silica sol is added, the blanket substrate may be lightly pressed to ensure that the blanket substrate is sufficiently impregnated in order to improve the bond between the blanket substrate and the catalyzed silica sol. After that, the blanket substrate may be pressed to a certain thickness with a certain pressure to remove excess sol and reduce the drying time.

[0045] According to one embodiment of the present invention, the catalyzed silica sol may be added in an amount of 80% by volume to 120% by volume, preferably 90% by volume to 110% by volume, based on the volume of the blanket substrate. Also, preferably, the amounts of the blanket substrate and the catalyzed silica sol added may satisfy the above-mentioned mutual addition ratio under the condition that the addition amount is satisfied for the above-mentioned reaction vessel. When the catalyzed silica sol satisfies the addition ratio (addition amount) with respect to the volume of the blanket substrate, the catalyzed silica sol is more uniformly impregnated into the blanket substrate, so that the manufactured aerogel blanket can have more uniform physical properties, and the catalyzed silica sol can be completely impregnated into the blanket substrate, so that loss of raw materials can be prevented, and the problem of the catalyzed silica sol gelling independently can be prevented.

[0046] According to one embodiment of the present invention, the catalyzed silica sol is impregnated into a blanket substrate to cause gelation, thereby obtaining a wet gel-fiber composite. The gelation may be the formation of a network structure from the catalyzed silica sol, and the network structure may be a planar network structure in which certain polygons having one or more types of atomic arrangements are connected, or a structure in which vertices, corners, faces, etc. of certain polyhedra are shared to form a three-dimensional framework structure.

[0047] According to one embodiment of the present invention, the gelation may be induced by impregnating the blanket substrate with the catalyzed silica sol and then leaving it for 0.5 to 2.0 hours. The gelation may be performed within a temperature range of 20°C to 50°C, and preferably at room temperature.

[0048] According to an embodiment of the present invention, the step 2) may be started after the step 1) is completed, and the steps 1) and 2) may be performed sequentially. According to another embodiment of the present invention, step 2) may be started and performed before the completion of step 1), and in such a case where step 2) is performed before the completion of step 1), the catalyzed sol may be charged in its entirety into the reaction vessel until gelation is completed, specifically, before gelation is completed.

[0049] Additional process: Aging process In the manufacturing method according to an embodiment of the present invention, an aging step may be additionally performed as a process for leaving the wet gel-fiber composite at a suitable temperature to complete chemical changes. The aging step can further strengthen the formed network structure, thereby enhancing the mechanical stability of the aerogel blanket of the present invention.

[0050] The aging step must be carried out in an appropriate temperature range to optimally strengthen the pore structure, and the aging step of the present invention may be carried out by leaving the mixture at a temperature of 30°C to 70°C for 3 hours to 50 hours. When the aging temperature is within the above temperature range, the productivity can be ensured by aging at an appropriate level, and loss due to evaporation of the organic solvent can be prevented. In addition, the aging time within the above range may be preferably 6 hours to 48 hours, more preferably 18 hours to 48 hours, as a range that satisfies the thermal conductivity and hydrophobicity.

[0051] In the aging step, it is not necessary to add an additional catalyst. If an additional basic catalyst is added in the aging step, the pH of the wet gel-fiber composite may become excessively high. This may cause a problem of the gel structure collapsing due to shrinkage in the drying step, and the fiber itself may be damaged. In addition, if an additional acid catalyst is added, a neutralization reaction may occur in the wet gel-fiber composite during the aging process. This may result in the loss of silanol groups that should be replaced with hydrophobic groups, decreasing the efficiency of surface modification. Therefore, it is preferable not to add an additional catalyst in the aging step.

[0052] Furthermore, according to one embodiment of the present invention, the aging step may be carried out in a separate reaction vessel after recovering the silica wet gel-fiber composite after gelation is completed, or may be carried out inside the reaction vessel in which gelation is carried out. In terms of process efficiency and simplification of the equipment, the aging step may be preferably carried out in the reaction vessel in which gelation is carried out.

[0053] Step 3: Surface modification process According to one embodiment of the present invention, step 3) is a step of hydrophobizing the wet gel-fiber composite prepared in step 2) by adding an acidic surface modification solution containing a surface modifier and a chlorine-based acid derivative aqueous solution.

[0054] When hydrophilic functional groups present on the surface of the aerogel are replaced with hydrophobic functional groups, the repulsive force between the hydrophobic functional groups can minimize the shrinkage of the pores due to the surface tension of the solvent when the aerogel is dried. The dried aerogel maintains low thermal conductivity immediately after drying, but has the disadvantage that the thermal conductivity gradually increases as the hydroxyl functional groups present on the surface of the aerogel (for example, in the case of silica aerogel, the hydrophilic silanol groups (Si-OH) present on the surface of the silica absorb water in the air. Therefore, in order to maintain low thermal conductivity, it is necessary to modify the surface of the aerogel to be hydrophobic.

[0055] Therefore, the surface modification according to one embodiment of the present invention may be performed by a surface modifying agent comprising a polar solvent and an organosilane compound. As the polar solvent, methanol, ethanol, isopropyl alcohol, or the like may be used, and as the organic silane compound, trimethylchlorosilane (TMCS), hexamethyldisilazane (HMDS), methyltrimethoxysilane (MTMS), trimethylethoxysilane (TMES), ethyltriethoxysilane (ETES), phenyltriethoxysilane (PTES), or the like may be used, and preferably, trimethylethoxysilane or hexamethyldisilazane may be used.

[0056] The surface modifier is preferably mixed in a volume ratio of 0.5 to 10.0 with respect to the wet gel in the case of a polar solvent, and in the case of an organosilane compound, in a volume ratio of 0.1 to 10.0 with respect to the wet gel. In the case of a surface modifier containing an organosilane compound and a polar solvent, the volume ratio may be 0.5 to 10.0 with respect to the wet gel. When the volume ratio of the organosilane compound with respect to the wet gel is less than 0.1, the reaction time becomes excessively long and the surface modification efficiency may decrease, and when the volume ratio of the organosilane compound exceeds 10.0, there is a problem of increased cost, and the unreacted surface modifier may induce shrinkage during drying.

[0057] The organic silane compound and the polar solvent may be mixed in such a volume ratio, and the surface modifier in the mixed state may contain the organic silane compound in an amount of 10% by volume to 60% by volume based on the total volume of the surface modifier. The content of the organic silane compound in the surface modifier may affect the hydrophobicity and thermal conductivity, and the higher the content, the more improved it may be. However, if it exceeds 60% by volume, there is no increase in the additional surface modification efficiency, and only the amount of waste organic silane compound increases, so the amount needs to be appropriately adjusted within the above range. In addition, in order to expect the above-mentioned effects and to minimize the deviation in the surface modification efficiency of the final aerogel blanket, i.e., the hydrophobicity degree, depending on the amount of the acid aqueous solution, the amount may be preferably 15% by volume to 50% by volume, more preferably 20% by volume to 50% by volume, and even more preferably 25% by volume to 50% by volume.

[0058] According to one embodiment of the present invention, the acidic surface-modifying solution further includes a chlorine-based acid derivative aqueous solution in addition to the surface modifier. The chlorine-based acid derivative aqueous solution may be diluted with an acid in an aqueous solution state, and may be diluted to a concentration of 10% by weight to 50% by weight, preferably 20% by weight to 40% by weight. The acidic surface-modifying solution is a mixture of the surface modifier, which is an organosilane compound, diluted with the polar solvent and the diluted chlorine-based acid in the aqueous solution phase, and the molar number of the acid in the acidic surface-modifying solution may be determined based on the sodium-based base catalyst in step 1).

[0059] Specifically, the molar ratio of the acid in the acidic surface modification solution may be 0.5 to 15 equivalents, preferably 1 to 10 equivalents, relative to the molar ratio of the sodium ion of the sodium-based base catalyst. When the molar ratio of the acid satisfies the above range, the pH can be set to an extremely acidic level so that the surface modification reaction conditions are acidic, thereby preventing the collapse of the gel structure that occurs under neutral or basic conditions, and functioning as a medium to promote the surface modification reaction. In this case, the pH may be in the range of 0.2 to 3.5, preferably 0.3 to 3.0, more preferably 0.5 to 2.5.

[0060] More specifically, when trimethylethoxysilane (TMES) is used as a surface modifier, when the acid aqueous solution is included in the surface modification solution, TMES modifies the (Si 3+ )(3OH - ) to perform surface modification, but in competition with this, TMES reacts with water to form hexadimethylsiloxane (HMDSO) and ethanol, and since hexadimethylsiloxane has a very stable structure, it cannot undergo a surface modification reaction with the silica gel surface, which reduces the surface modification efficiency, and this can cause the gel structure to collapse due to shrinkage during the drying process. However, when a chlorine-based acid-derived aqueous solution is added, for example, when a hydrochloric acid aqueous solution is added, the reaction between TMES and hydrochloric acid can occur competitively over the reaction between TMES and water, and trimethylchlorosilane (TMCS) can be formed by the reaction between TMES and hydrochloric acid. This TMCS is an organic silane compound that functions as a surface modifier that can perform a surface modification reaction like TMES, so the surface modification efficiency can be maximized. In other words, it suppresses the formation of HMDSO and ethanol, which deteriorate the surface modification efficiency, and also performs a reaction to generate a surface modifier, so the surface modification efficiency can be maximized compared to when it is not added. As described above, the degree of activation of this mechanism may vary depending on the equivalent ratio of the acid to the base catalyst, and the effect can be maximized when the acid is added to the acidic surface modification solution so as to satisfy the above-mentioned range.

[0061] Specifically, the chlorine-based acid derived aqueous solution may refer to one that contains a chlorine-based acid or one that can generate a chlorine-based acid in the aqueous solution phase. For example, the chlorine-based acid derived aqueous solution may be an aqueous solution containing hydrochloric acid, trimethylchlorosilane, dimethyldichlorosilane, or methyltrichlorosilane. When a nitrogen-based acid or a sulfur-based acid is used instead of a chlorine-based acid, the TMCS cannot be formed by the above mechanism, and therefore the surface modification efficiency may decrease, resulting in a low degree of hydrophobization.

[0062] In the manufacturing method according to one embodiment of the present invention, the surface modification step of step 3) may be performed for 10 to 50 hours, preferably 15 to 50 hours, more preferably 18 to 48 hours, and even more preferably 24 to 48 hours. The time for performing the surface modification step as described above is for obtaining an appropriate degree of hydrophobicity, and it is preferable to perform the surface modification step within the above range in order to achieve a certain level or higher of thermal conductivity and hydrophobicity of the final aerogel blanket.

[0063] The surface modification step may be carried out in a separate reaction vessel after recovering the silica wet gel-fiber composite that has been subjected to gelation or aging, or may be carried out inside the reaction vessel in which gelation or aging has been carried out. From the viewpoint of process efficiency and simplification of the apparatus, it is preferable that the aging and surface modification steps be carried out in the reaction vessel in which gelation or aging has been carried out. After the above surface modification step, a hydrophobic wet gel-fiber composite can be obtained.

[0064] Additional process: cleaning process In the method according to an embodiment of the present invention, a washing step may be further performed after the surface modification step and before the drying step, in order to remove impurities (sodium ions, unreacted materials, by-products, salts, etc.) generated during the reaction to obtain a highly pure hydrophobic silica aerogel.

[0065] The washing may be performed using ethanol or ethanol and an acidic aqueous solution. In the surface modification step, a salt can be generated by a neutralization reaction between the sodium-based base catalyst used in the gelation and the acidic surface modification solution, and sodium ions can be easily removed by the generation of the salt. When the washing by the neutralization reaction is performed using an acidic aqueous solution, the neutralization reaction performed in the surface modification step induces the generation of the salt, and the effect of removing impurities can be further maximized, and in this case, the degree of hydrophobicity can be further improved.

[0066] The acid aqueous solution may be the same as the acid aqueous solution contained in the acidic surface modification solution in the surface modification step, and the washing may be repeated several times. However, if the washing is repeated too many times, it is necessary to appropriately control the number of times considering that the hydrophobic group may be released.

[0067] Step 4: Drying According to one embodiment of the present invention, the hydrophobized wet gel-fiber composite obtained by step 3) is dried to produce a hydrophobic aerogel blanket.

[0068] The drying step according to an embodiment of the present invention may be performed by removing the solvent while maintaining the pore structure of the aged gel, and may be performed by a supercritical drying or atmospheric drying process.

[0069] The supercritical drying process may be performed using supercritical carbon dioxide. Carbon dioxide (CO2) is in a gaseous state at room temperature and pressure, but when it exceeds a certain temperature and pressure limit called the supercritical point, it enters a critical state where it is indistinguishable between gas and liquid because the evaporation process does not occur. Carbon dioxide in this critical state is called supercritical carbon dioxide.

[0070] Supercritical carbon dioxide has molecular density close to that of a liquid, but low viscosity, so it has properties close to that of a gas. It also has fast diffusion and high thermal conductivity, so it has high drying efficiency and can shorten the drying process time.

[0071] Specifically, the supercritical drying process is a solvent replacement process in which the aged wet gel blanket is placed in a supercritical drying reactor, and then liquid CO2 is filled in to replace the alcohol solvent inside the wet gel with CO2. Thereafter, the temperature is raised to 40°C to 70°C at a constant heating rate, specifically at a rate of 0.1°C / min to 1.0°C / min, and then a pressure equal to or higher than the pressure at which carbon dioxide becomes supercritical, specifically at a pressure of 100 bar to 150 bar, is maintained, and the carbon dioxide supercritical state is maintained for a certain period of time, specifically 20 minutes to 1 hour. Generally, carbon dioxide becomes supercritical at a temperature of 31°C and a pressure of 73.8 bar. After maintaining a constant temperature and pressure at which carbon dioxide becomes supercritical for 2 hours to 12 hours, more specifically 2 hours to 6 hours, the pressure is gradually removed to complete the supercritical drying process and produce an aerogel blanket.

[0072] In the case of the normal pressure drying step, the step may be carried out at a temperature of 70° C. to 200° C. under normal pressure (1±0.3 atm) by a conventional method such as hot air drying, IR drying, or oven drying.

[0073] According to an embodiment of the present invention, the manufacturing method preferably includes drying at normal pressure. Although supercritical drying may be performed, it is effective in removing the solvent without collapsing the gel structure because it requires high-pressure equipment and it is difficult to control various process conditions, which significantly increases the unit price of the product. However, when the manufacturing method of the present invention is applied, it is advantageous in that it is not necessary to perform the supercritical drying process that requires high-pressure equipment because it is possible to prevent the gel structure from collapsing even if normal pressure drying is applied without applying supercritical drying, and it is possible to obtain an effect equivalent to that of supercritical drying only by drying at normal pressure.

[0074] As a result of the drying process, a blanket containing porous aerogel having nano-sized pores can be manufactured. In particular, the silica aerogel according to one embodiment of the present invention has excellent physical properties, particularly low tap density and high porosity, along with a high degree of hydrophobicity, and a silica aerogel-containing blanket containing the same has excellent mechanical flexibility along with low thermal conductivity.

[0075] In addition, before or after the drying process, a pressing process for adjusting the thickness and making the internal structure and surface shape of the blanket uniform, a molding process for providing an appropriate shape or morphology depending on the application, or a lamination process for laminating another functional layer may be further performed.

[0076] When an aerogel blanket is manufactured by the manufacturing method as described above, it is not necessary to carry out a solvent replacement process to remove impurities and to replace the solvent with one that is easily volatile, so that the process can be easily simplified. Furthermore, even without an additional cleaning process, an aerogel blanket with sufficiently excellent physical properties can be provided, so that the degree of freedom in process design for process simplification can be sufficiently ensured.

[0077] 3. Aerogel Blanket The present invention provides an aerogel blanket having uniform thermal conductivity and hydrophobicity, and particularly excellent hydrophobicity. Specifically, the aerogel blanket may have a short-term hydrophobicity of 4.0% or less, a long-term hydrophobicity of 26.0% or less, preferably a short-term hydrophobicity of 3.5% or less, a long-term hydrophobicity of 25.4%, more preferably a short-term hydrophobicity of 2.5% and a long-term hydrophobicity of 22.0%, and even more preferably a short-term hydrophobicity of 2.0% or less and a long-term hydrophobicity of 20.0% or less. In addition, the ratio of the short-term hydrophobicity to the long-term hydrophobicity (short-term hydrophobicity / long-term hydrophobicity) may be 15.0% or less, preferably 13.0% or less, more preferably 12.0% or less, and even more preferably 10.0% or less, in percentage. Here, the short-term hydrophobicity and the long-term hydrophobicity are derived by the following measurement method.

[0078] According to ASTM C1511, a test piece measuring 25.4cm x 25.4cm is floated on distilled water at 21±2℃, and a 6.4mm mesh screen is placed on the test piece and submerged 127mm below the water surface. After 15 minutes (short term) and 96 hours (long term), the screen is removed, and when the test piece floats up, the test piece is removed with a clamp. Next, the aerogel test piece is removed and the surface water is absorbed by a wiper for 2 seconds according to ASTM C1763. During this process, the weight is measured before and after the surface water is removed after impregnation, and the weight increase rate is calculated, and the average value of three test pieces is defined as the short-term and long-term hydrophobicity.

[0079] The aerogel blanket according to one embodiment of the present invention is manufactured by the above-mentioned manufacturing method, and therefore has an excellent level of hydrophobicity, i.e., a very low moisture absorption rate, and the moisture absorption rate increases only to a low degree even when exposed to moisture for a long period of time, so that the aerogel blanket can have an excellent hydrophobicity and can also have excellent thermal conductivity.

[0080] The aerogel blanket of the present invention can be usefully used as a heat insulating material, heat retaining material, or non-combustible material for aircraft, ships, automobiles, building structures, etc., as well as for heat and cold insulating plant facilities such as piping in various industrial facilities and industrial furnaces.

[0081] Working Example DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings, in which: FIG. 1 is a schematic diagram of a semiconductor device according to an embodiment of the present invention;

[0082] Example 1 The reactor is mixed with prehydrolyzed TEOS (silica content = 20.1 wt%, HTEOS) and ethanol (water content 8 wt%), with a target density of 70 kg / m 3 The mixture was mixed so that the silica sol was prepared. Sodium hydroxide (NaOH) with a concentration of 33% was added as a sodium-based base catalyst, and the molar concentration of sodium ions was 10 mmol / L relative to the volume of the silica sol to prepare a catalyzed silica sol. Glass fiber (glass fiber mat, 10 mm) was added as a blanket substrate in the reactor containing the catalyzed silica sol, and the blanket substrate was impregnated with the silica sol. The mixture was left in a sealed state for 1 hour to gel, obtaining a wet gel-fiber composite, which was then heated to 60°C and left for 24 hours to be aged.

[0083] Then, a solution of trimethylethoxysilane diluted with ethanol (water content 8% by weight) to 40% by volume was prepared in the same volume ratio as the wet gel-fiber composite, and 50 mmol / L aqueous hydrochloric acid was added to the solution so that the amount of hydrochloric acid in the acidic surface modification solution was 5 equivalents based on the molar concentration of the sodium ions in the sodium-based base catalyst, producing an acidic surface modification solution. This was added to a reactor and hydrophobized at 60°C for 24 hours. Finally, the mixture was oven-dried at 150° C. and atmospheric pressure for 1 hour to produce a silica aerogel blanket.

[0084] Examples 2 to 14 and Comparative Examples 1 to 9 A silica aerogel blanket was manufactured in the same manner as in Example 1, except that the conditions were changed as shown in Table 1 below.

[0085] [Table 1]

[0086] 1) SS: Sodium silicate 2) Ammonia input: 35mmol / L

[0087] Experimental Example 1) Thermal conductivity at room temperature (mW / mK) and thickness (mm) Five samples each having a size of 30 cm x 30 cm were prepared for each aerogel blanket manufactured in each Example and Comparative Example, and the thermal conductivity of the samples was measured at room temperature (23 ± 5 ° C.) using a NETZSCH HFM 436 Lambda device. In this case, the five samples were obtained by cutting the aerogel blanket roll manufactured in each Example and Comparative Example at regular intervals of 50 cm from the innermost to the outermost. The thermal conductivity of each of the five samples was measured.

[0088] The thermal conductivity is measured by a heat flux transducer in the device that measures the heat flow of a sample placed between a hot plate and a cold plate, and a calibration factor (N) can be obtained from a reference material with a known thermal conductivity value. The calculated thermal conductivity can be obtained from this N value and the measured heat flow of the sample. During this process, the thickness of the sample is also derived as a measurement value.

[0089] 2) Short-term moisture impregnation rate (wt%) The water absorption rate of the silica aerogel blankets produced in each of the examples and comparative examples was measured.

[0090] Specifically, in accordance with ASTM C1511, a test piece measuring 25.4cm x 25.4cm was floated on distilled water at 21±2°C, and a 6.4mm mesh screen was placed on top of the test piece and submerged 127mm below the water surface. After 15 minutes, the screen was removed and the test piece floated up, and then the test piece was clamped and hung vertically for 60±5 seconds. The weights were then measured before and after soaking, and the above process was repeated for three test pieces per sample to determine the average weight increase rate, which was shown as the water absorption rate when the surface water was not removed.

[0091] In accordance with ASTM C1763, an aerogel test piece was taken out and the surface moisture was absorbed by a wiper for 2 seconds, after which the weight was measured. The average weight increase rate of three test pieces before and after the surface water was removed was shown as the moisture absorption rate when the surface water was removed. The lower the moisture absorption rate, the higher the hydrophobicity of the aerogel blanket.

[0092] 3) Long-term moisture impregnation rate (wt%) The water absorption rate of the silica aerogel blankets produced in each of the examples and comparative examples was measured.

[0093] Specifically, in accordance with ASTM C1511, a test piece measuring 25.4cm x 25.4cm was floated on distilled water at 21±2°C, and a 6.4mm mesh screen was placed on top of the test piece and submerged 127mm below the water surface. After 96 hours, the screen was removed and the test piece floated up, and then the test piece was clamped and hung vertically for 60±5 seconds. The weights were then measured before and after soaking, and the above process was repeated for three test pieces per sample to determine the average weight increase rate, which was shown as the water absorption rate when the surface water was not removed.

[0094] In accordance with ASTM C1763, an aerogel test piece was taken out and the surface moisture was absorbed by a wiper for 2 seconds, after which the weight was measured. The weights of three test pieces were measured before and after the surface moisture was removed, and the average weight increase rate was shown as the moisture absorption rate when the surface moisture was removed. The lower the moisture absorption rate, the higher the hydrophobicity of the aerogel blanket.

[0095] [Table 2]

[0096] Referring to Table 2, it is confirmed that in the cases of Examples 1 to 14, the thermal conductivity is low and the short-term and long-term moisture impregnation rates are low, and therefore excellent effects as a heat insulating material are realized. In contrast, in the cases of Comparative Examples 1 to 4, where hydrochloric acid is not used, even if the concentration of the surface modifier is changed, the thermal conductivity is high, and therefore it is confirmed that the performance of the heat insulating material is not appropriate. It can be confirmed that the hydrophobicity is also at a poor level in both the short term and long term, and in particular, moisture penetrates deep inside the aerogel blanket, and even if the surface water is removed, the difference is not large, so it is not easy to remove the impregnated moisture. In addition, in the cases of Comparative Examples 5 and 6, where an ammonia catalyst is used as in the past, the thermal conductivity and short-term hydrophobicity are similar to those of the Examples, but the long-term hydrophobicity is poor, and it can be confirmed that a large amount of moisture is impregnated inside rather than on the surface, and that the moisture is difficult to remove.

[0097] Furthermore, in Comparative Examples 7 and 8, nitric acid was used instead of hydrochloric acid in the acidic surface modification solution, and it was confirmed that when nitric acid was used, whether ammonia or sodium hydroxide was used as a base catalyst, there was no effect on the physical properties. This confirmed that there was a synergistic effect between sodium hydroxide and hydrochloric acid in the acidic surface modification solution.

Claims

1. 1) mixing a silica sol and a sodium-based base catalyst to obtain a catalyzed silica sol having a pH of 9.0-11.0; 2) impregnating a blanket substrate with the catalyzed silica sol to form a gel, thereby obtaining a wet gel-fiber composite; 3) adding an acidic surface modification solution containing a surface modifier and a chlorine-based acid derivative aqueous solution to the wet gel-fiber composite to hydrophobize it; 4) drying the hydrophobized wet gel-fiber composite; Including, The chlorine-based acid derived aqueous solution is introduced so that the number of moles of acid in the aqueous solution is 1 equivalent to 10 equivalents relative to the number of moles of sodium ions of the sodium-based base catalyst.

2. 2. The method for producing an aerogel blanket according to claim 1, wherein the sodium-based base catalyst is an aqueous solution containing at least one of sodium hydroxide and sodium silicate.

3. 3. The method for producing an aerogel blanket according to claim 1, wherein the silica sol comprises a silica precursor and an organic solvent.

4. The method for producing an aerogel blanket according to any one of claims 1 to 3, wherein in step 2), the catalyzed silica sol is used in an amount of 80% by volume to 120% by volume based on the volume of the blanket substrate.

5. The method for producing an aerogel blanket according to any one of claims 1 to 4, wherein the chlorine-based acid derived aqueous solution is an aqueous solution containing one or more selected from the group consisting of hydrochloric acid, trimethylchlorosilane, dimethyldichlorosilane, and methyltrichlorosilane.

6. The method for producing an aerogel blanket according to any one of claims 1 to 5, wherein the surface modifier is an organic silane compound diluted in an organic solvent to 10% by volume to 50% by volume.

7. 7. The method for producing an aerogel blanket according to claim 6, wherein the organosilane compound is at least one selected from the group consisting of trimethylchlorosilane (TMCS), hexamethyldisilazane (HMDS), methyltrimethoxysilane (MTMS), trimethylethoxysilane (TMES), ethyltriethoxysilane (ETES), and phenyltriethoxysilane (PTES).

8. The method for producing an aerogel blanket according to any one of claims 1 to 7, further comprising a step of aging after step 2).

9. The method for producing an aerogel blanket according to claim 8, wherein the aging is carried out at a temperature of 40°C to 80°C for 6 hours or more.

10. The method for producing an aerogel blanket according to any one of claims 1 to 9, further comprising the step of washing with ethanol or an acid aqueous solution after step 3).

11. The method for producing an aerogel blanket according to any one of claims 1 to 10, wherein the drying in step 4) is carried out by a normal pressure drying process at a pressure of 1±0.3 atm and a temperature of 70°C to 200°C.

12. The method for producing an aerogel blanket according to any one of claims 1 to 11, wherein the blanket substrate is a porous substrate.

Citation Information

Patent Citations

  • Preparation method of oxidized graphene modified silicon dioxide aerogel fiber product adjustable in hydrophobic and hydrophilic property

    CN108793943A

  • Airgel composites, methods of making and uses thereof

    JP1998504792A

  • Method for producing organically modified aerogel

    JP2012144428A

  • Manufacturing method of hydropobic silica aerogel powder with insulating performance

    KR1020120070948A

  • Thermal insulation sheet and manufacturing method therefor

    WO2017159438A1